Development of the World View and Values of Technical University Students in the Context of Spiritual and Moral Education - Mykhailo Palahniuk; Kateryna Fomin (Vasyl Stefanyk Precarpathian National University, 2023)
The article highlights the importance of the social and humanitarian disciplines, related to the spiritual and moral aspects of a young person's life to face the challenge of preserving the individual's integrity and spiritual growth in modern conditions of stressful, emotional, and psychological overload. It is impossible to implement it in practice without introducing new and improving existing paradigms of spiritual and moral upbringing in educational institutions, which is carried out precisely in the process of teaching social and humanitarian disciplines. The problem of spiritual and moral education of the individual has always been one of the relevant ones, and in the current conditions of the coronavirus pandemic, russia's military aggression and Ukraine's struggle for peace, and the European values of democracy, it acquires special importance. After all, in the process of radical socio-political, economic, and cultural reforms of society, the challenge of increasing the role of future specialists training concerning the demands of modern social development and humanization of the educational process generally requires scientists and teachers' significant attention. The article outlines the main ideals and educational guidelines of Ukrainian society, as they embody the real revival and further development of the Ukrainian nation. The authors emphasize the fact that instability and inconsistency of the moral atmosphere in Ukrainian society resulted in the spiritual and moral education of the young generation becoming particularly acute. This process encourages the revival of tradition and the search for innovative means of spiritual and moral education for Ukrainian youth. The key conditions regarding the importance of spiritual and moral education of future specialists are given.